Epidemiology of Pandemic COVID-19 and Its Association with Some Chronic Diseases in Sulaimani City, Iraq - Maulood, Shaxawan Azeez; Mina, Muhammed Babakir; Ali, Salar Ibrahim (Kurdistan Journal of Applied Research, 2022)
The study aims to provide the epidemiological characteristics of the COVID-19 patients who admitted to Shahid Dr Hemin Teaching Hospital in Sulaimani city, Iraq. It is a cross-sectional study, the data were collected by a convenience sampling method in the hospital, which started from 2nd October to 31th of December 2020. The current study included all the patients who admitted to the hospital, which involved 371 patients. The data were collected from patient’s medical record and a direct interview method was used for filling in the questionnaire form. The collected data were analysed by the SPSS program to produce descriptive statistics such as frequency, percentage, mean and standard deviation while Chi-square test used to find out the association between variables with considering a p-value ? 0.05 as a significant interpretation. The results show that the age of hospitalized COVID-19 patients ranges from 19-95 years old with mean of (63.69±12.73). The age of majority of patients 159 (42.9%) was between 65-79 years old followed by 50-64 years old 124 (33.4%). Male to female ratio was 2:1. Most of the patients were retired 119 (32.1%) in comparison to other occupations and illiterate patients 151(40.7%) were dominance over other patient’s education levels. In addition, majority of patients had hypertension 278(74.9%), diabetes 132 (35.6%) and cardiovascular disease (CVD) 130 (35.0%) and 230 (62.0%) and 141(38.0%) of them were in severe and moderate stage of disease respectively. Also, there was a significant association between the patient’s age group and patients’ outcome while for gender, occupation, and education level, stage of the disease, there were non-significant. The presence of CVD, hypertension and diabetes increase the mortality rate among the patients. In conclusion, age of COVID-19 patient has a great impact on increasing mortality rate and the presence of comorbidities among the patients significantly raise the mortality rate of COVID-19.